The MdNAC72-MdABI5 module acts as an interface integrating jasmonic acid and gibberellin signals and undergoes ubiquitination-dependent degradation regulated by MdSINA2 in apple - Li, Hong-Liang (The New phytologist, 2024)
© 2024 The Authors. New Phytologist © 2024 New Phytologist Foundation.